2021
DOI: 10.1097/jxx.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Organizational empowerment and practice outcomes of acute care nurse practitioners in Taiwan: A national survey

Abstract: Background: Nurse practitioners (NPs) play an important role in addressing growing health care needs. Among NPs, organizational empowerment is positively associated with overall practice outcomes. Therefore, efforts to promote organizational empowerment in practice are necessary to increase job satisfaction among NPs as well as decrease the stress and intention to leave. Purpose: This study investigated the relationships of organizational empowerment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…We used the TANP database to ensure all eligible NPs were approached. Nevertheless, this comes with the issue of a 20.19% response rate, which is comparable with other survey designs (Luo et al, 2021). Thus, the representativeness of the sample might be minimal and there might be sampling bias.…”
Section: Limitationsmentioning
confidence: 78%
See 4 more Smart Citations
“…We used the TANP database to ensure all eligible NPs were approached. Nevertheless, this comes with the issue of a 20.19% response rate, which is comparable with other survey designs (Luo et al, 2021). Thus, the representativeness of the sample might be minimal and there might be sampling bias.…”
Section: Limitationsmentioning
confidence: 78%
“…Brown et al (2019) pointed out that organisations with high organisational commitment are more likely to develop a healthy organisational climate, which motivates staff to achieve common goals and cohesion in the organisation, because they are empowered in their practice. Study results revealed that NPs perceived insufficient levels of organisational commitment for acute care practices, which might be explained by regulations requiring NPs to be supervised by and collaborate with physicians as they practice in Taiwan (Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations